Peningkatan Hasil Belajar Volume Kubus dan Balok Dengan Pendekatan Pendidikan Matematika Realistik di Sekolah Dasar - Bastian, Revany Yeno (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research, the writer apply PMR approach to improve student learning outcomes. The purpose is to describe the planning, execution, and improvement of learning outcomes in primary school 38 Lubuk Sao Agam. This type of research is a classroom action research, with qualitative approaches and quantitative approaches that consist of two cycles. The research appears that student learning outcomes increased from KKM set is 70. In the first cycle of lesson planing get anaverase value of 81.85% to 96,43%, teacher activity 71,87% to 84,38%, student activity 76,56% to 87,5%, and student learning outcomes 74.37 to 82. In short, PMR can improve student learning outcomes in the learning process the volume of cubes and blocks. Kata Kunci : hasil belajar, volume kubus dan balok, PMR.